2016
DOI: 10.1371/journal.pone.0167557
|View full text |Cite
|
Sign up to set email alerts
|

Specific Stimuli Induce Specific Adaptations: Sensorimotor Training vs. Reactive Balance Training

Abstract: Typically, balance training has been used as an intervention paradigm either as static or as reactive balance training. Possible differences in functional outcomes between the two modalities have not been profoundly studied. The objective of the study was to investigate the specificity of neuromuscular adaptations in response to two balance intervention modalities within test and intervention paradigms containing characteristics of both profiles: classical sensorimotor training (SMT) referring to a static ledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 87 publications
5
32
1
1
Order By: Relevance
“…As a consequence, RBT requires an accurate repositioning of the center of mass (COM) utilizing rapid and appropriate neuromuscular responses to regain a stable body position after surface translation. Thus, RBT may challenge reactive postural stability more than CBT ( Horstmann and Dietz, 1990 ; Yim-Chiplis and Talbot, 2000 ) and may be more effective as an intervention to counteract falls ( Freyler et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, RBT requires an accurate repositioning of the center of mass (COM) utilizing rapid and appropriate neuromuscular responses to regain a stable body position after surface translation. Thus, RBT may challenge reactive postural stability more than CBT ( Horstmann and Dietz, 1990 ; Yim-Chiplis and Talbot, 2000 ) and may be more effective as an intervention to counteract falls ( Freyler et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on perturbation-based balance training (PBT), specific improvements in dynamic and perturbed balance tasks are observed, as expected, but no or minimal changes are seen in less dynamic or static balance tasks (Freyler et al, 2016, Chien and Hsu, 2018, Krause et al, 2018, although one study has reported beneficial transfer effects from PBT to standing balance (Kurz et al, 2016). Accordingly, it is not surprising that PBT leads to better performance of rapid balance control tasks than traditional proactive balance control training (Freyler et al, 2016) and Tai-Chi training (Aviles et al, 2019). As discussed in Chapter 5.1, PBT for falls prevention concords more to the principles of specificity in training and learning than does traditional balance training, so these results should not be surprising, and I recently attempted to recapitulate this: "We do not expect athletes to win Olympic medals without practising the skills of their sports, so why should we expect older adults to fall less often without practising the skills required for avoiding falls?"…”
Section: 221: Specificitysupporting
confidence: 54%
“…One systematic review has demonstrated a task-specific effect of balance training in healthy adults and children, whereby trained tasks improve with practice, but untrained tasks do not generally improve (Kummel et al, 2016). In studies on perturbation-based balance training (PBT), specific improvements in dynamic and perturbed balance tasks are observed, as expected, but no or minimal changes are seen in less dynamic or static balance tasks (Freyler et al, 2016, Chien and Hsu, 2018, Krause et al, 2018, although one study has reported beneficial transfer effects from PBT to standing balance (Kurz et al, 2016). Accordingly, it is not surprising that PBT leads to better performance of rapid balance control tasks than traditional proactive balance control training (Freyler et al, 2016) and Tai-Chi training (Aviles et al, 2019).…”
Section: 221: Specificitymentioning
confidence: 88%
“…Third, lack of a comparison group receiving only treadmill training may raise concerns on whether the effects of the training were attributable to both PBT and treadmill training (Steib et al, 2017;Handelzalts et al, 2019). However, the more pronounced neuromuscular modulation effects with the addition of perturbation to balance training compared with conventional balance training were reported previously (Freyler et al, 2016;Krause et al, 2018). In addition, the effectiveness of PBT may be challenged without the follow-up assessment for the control group.…”
Section: Study Limitationsmentioning
confidence: 99%